Adaptation of a Digital Signage Solution for repurposed TVBox Devices - Araujo, Luiz F. B. de; Oyamada, Marcio; Galante, Guilherme (Anais do Workshop on Sustainable Computing and Technology Reuse (SCoRe), 2025)
The dissemination of information via digital displays has become common in public places and in enclosed spaces with large numbers of people. With the increasing number of displays, local management of content becomes impractical, so flexible digital signage solutions with remote management and availability of content on a server are required. This paper presents the customization of an open source Xibo digital signage system. The focus is on adapting the client for 32- and 64-bit ARM architectures so that it can run on reused TV boxes. This solution is not only environmentally friendly, but also provides a cost-effective solution for deploying digital signage solutions by reusing devices that would otherwise be destroyed.